Electrolyte of high-voltage lithium ion battery and application of electrolyte
By using an electrolyte containing 3,3-trifluoroethylmethanesulfonate and 3,3-trifluoromethanesulfonate in a lithium-ion battery, a stable inorganic positive electrode electrolyte is formed by combining lithium-fluorosulfonylimide. The mesophase and graphite surface SEI film solve the problems of unstability and side reactions of traditional electrolytes at high voltages, and realizes the long-term cycle stability and safety of lithium-ion batteries at high cutoff voltages.
Patent Information
- Application Number
- CN202411486897.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional lithium-ion batteries have low and unstable oxidation potential of electrolyte solvents at high voltages, resulting in side reactions and transition metal dissolution, reducing battery performance. The CEI film of the existing improved method has high interface resistance and lacks self-healing ability at high voltages. Limited performance improvement.
Using an electrolyte containing 2,2,2-trifluoroethylmethanesulfonate and/or 2,2,2-trifluoroethyltrifluoromethanesulfonate, combined with lithium bisfluorosulfonimide to form a rich The inorganic positive electrode electrolyte mesophase and the graphite surface SEI film with good stability suppress side reactions and expand the battery limit.
Keep the electrolyte stable under high voltage conditions, significantly reducing the side reaction between the positive electrode and the electrolyte, ensuring the long-term cycle stability of the lithium-ion battery under high cutoff voltage, and improving the energy density and safety of the battery.
Smart Images

Figure CN119230954A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to an electrolyte for a high-voltage lithium-ion battery and its application. Background Art
[0002] Increasing the cut-off voltage is one of the methods to improve the energy density of lithium-ion batteries. However, the solvents of traditional electrolytes (such as chain carbonates (dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC)), cyclic carbonates (propylene carbonate (PC), ethylene carbonate (EC))) have low oxidation potentials and cannot exist stably under high voltages. They decompose when the voltage is greater than 4.3V. In addition, traditional electrolytes will also have serious side reactions with the de-lithium electrode under high voltages, causing the transition metal to dissolve from the positive electrode and undergo structural reconstruction, thereby reducing battery performance.
[0003] Many methods have been developed to improve cathode-electrolyte compatibility. For example, surface coating or doping of the cathode can reduce the rate of side reactions between the electrolyte and the cathode. However, the CEI films formed by these methods have high interfacial resistance at high voltages and lack self-healing ability, resulting in limited performance improvements.
[0004] Therefore, there is an urgent need to provide an electrolyte suitable for high-voltage lithium-ion batteries. Summary of the invention
[0005] The present invention solves one of the problems of the related art from at least the following aspects.
[0006] An embodiment of the first aspect of the present application provides an electrolyte comprising a solvent and a lithium salt, wherein the solvent comprises 2,2,2-trifluoroethyl methanesulfonate (TM) and / or 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
[0007] In some embodiments, the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI).
[0008] In some embodiments, the electrolyte contains 0.5 to 6 mol / L of lithium salt.
[0009] In some embodiments, the electrolyte contains 0.5 to 3 mol / L of lithium salt.
[0010] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
[0011] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (5:1) to (1:5).
[0012] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (3:1) to (1:2).
[0013] An embodiment of the second aspect of the present application provides an application of the electrolyte of any embodiment of the first aspect in a high-voltage battery.
[0014] In some embodiments, the positive active material of the high voltage battery includes LCO or NCM811.
[0015] In some embodiments, the negative active material of the high voltage battery includes graphite.
[0016] In some embodiments, the charging cut-off voltage of the high voltage battery is greater than 4.3V.
[0017] An embodiment of the third aspect of the present application provides a high-voltage battery, comprising the electrolyte of any embodiment of the first aspect.
[0018] In some embodiments, the positive active material of the high voltage battery includes LCO or NCM811.
[0019] In some embodiments, the negative active material of the high voltage battery includes graphite.
[0020] In some embodiments, the charging cut-off voltage of the high voltage battery is greater than 4.3V.
[0021] Compared with the related art, the embodiments of the present application achieve at least the following beneficial effects:
[0022] The electrolyte provided in the embodiment of the present application can not only maintain stability under high voltage conditions, but also form an inorganic-rich positive electrode electrolyte interphase (CEI) on the high-voltage positive electrode, significantly reducing the side reaction of the electrolyte with the de-lithium positive electrode material under high voltage conditions. In addition, the electrolyte provided in the embodiment of the present application can also generate a SEI film with good stability and low impedance on the surface of the negative electrode graphite, ensuring the long-term cycle stability of LCO and NCM811 batteries at high cut-off voltages.
[0023] The electrolyte provided in the embodiment of the present application has strong oxidation stability, and by forming S (Li 2 SO x)CEI membrane suppresses the lithium desorption cathode side reactions (transition metal dissolution, gas evolution, etc.) under high voltage conditions, extending the limits of high-voltage batteries, allowing batteries such as graphite||LCO with a cut-off voltage of 4.55V and rechargeable graphite||NCM811 with a cut-off voltage of 4.6V to remain stable for thousands of cycles while maintaining good safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the O1 spectrum of the positive electrode surface of the graphite||NCM811 soft-pack battery using the electrolyte prepared in Example 1.
[0025] Figure 2 This is the EIS impedance spectrum of the graphite||NCM811 soft-pack battery using the electrolyte prepared in Example 1, Comparative Example 1, and Comparative Example 2 after 1000 cycles.
[0026] Figure 3 The oxidation stability of the electrolyte prepared in each example was tested for LSV.
[0027] Figure 4 The oxidation stability of the electrolytes prepared in Example 1 and Comparative Example 2 was tested for LSV.
[0028] Figure 5 The cycling stability of graphite||NCM811 soft-pack batteries using the electrolytes prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 5 at a cut-off voltage of 4.6V, a charge rate of 1C, and a discharge rate of 2C.
[0029] Figure 6 The cycling stability of graphite||LCO soft-pack batteries using the electrolytes prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 5 at a cut-off voltage of 4.55V, a charge rate of 1C, and a discharge rate of 2C. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments. The examples provided are only for illustrating the present invention and are not intended to limit the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art and are not intended to limit the present invention in any way.
[0031] This application is made based on the following knowledge of the inventor:
[0032] Increasing the cut-off voltage is one of the methods to improve the energy density of lithium-ion batteries. However, the solvents of traditional electrolytes (such as chain carbonates (dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC)), cyclic carbonates (propylene carbonate (PC), ethylene carbonate (EC))) have low oxidation potentials and cannot exist stably under high voltages. They decompose when the voltage is greater than 4.3V. In addition, traditional electrolytes will also have serious side reactions with the de-lithium electrode under high voltages, causing the transition metal to dissolve from the positive electrode and undergo structural reconstruction, thereby reducing battery performance.
[0033] Many methods have been developed to improve cathode-electrolyte compatibility. For example, surface coating or doping of the cathode can reduce the rate of side reactions between the electrolyte and the cathode. However, the CEI films formed by these methods have high interfacial resistance at high voltages and lack self-healing ability, resulting in limited performance improvements.
[0034] Electrolyte design that can form high-quality CEI films in situ is a more promising solution. Hydrofluoroethers, fluorobenzenes, fluorinated sulfones, and fluorinated carbonates have excellent oxidative stability. However, the short shelf life of fluorinated electrolytes and the increase in interfacial impedance during use limit their applicability. Although additives can further protect the cathode by sacrificial decomposition to form a protective CEI, the CEI is in a dynamic process of formation, destruction, and repair, so a small amount of additives cannot maintain interfacial stability during long-term cycling. High-concentration electrolytes (HCE), locally high-concentration electrolytes (LHCE), and weakly solvated electrolytes also improve oxidative stability by forming inorganic-rich CEI / SEI. However, to date, the charge cutoff voltages reported in these electrolytes are mostly limited to 4.5 V (relative to Li + / Li).
[0035] Based on this, the inventors of the present application designed a multifunctional solvent molecule by integrating the advantages of an additive (PS) and a lithium salt (LiOTf) into a solvent, thereby obtaining a fluorinated sulfonate electrolyte for high-voltage lithium-ion batteries.
[0036] An embodiment of the first aspect of the present application provides an electrolyte comprising a solvent and a lithium salt, wherein the solvent comprises 2,2,2-trifluoroethyl methanesulfonate (TM) and / or 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
[0037] In some embodiments, the lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI).
[0038] In some embodiments, the electrolyte contains 0.5 to 6 mol / L (e.g., 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L) of lithium salt.
[0039] In some embodiments, the electrolyte comprises 0.5 to 3 mol / L (eg, 1 mol / L, 1.5 mol / L, 2 mol / L, 5.2 mol / L) of lithium salt.
[0040] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
[0041] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (5:1) to (1:5) (e.g., 5:1, 4:1, 3:1, 2:1, 1:1, 5:2, 4:2, 3:2, 2:2, 1:2, 5:3, 4:3, 3:3, 2:3, 1:3, 5:4, 4:4, 3:4, 2:4, 1:4, 5:5, 4:54, 3:5, 2:5, 1:5).
[0042] In some embodiments, the solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (3:1) to (1:2) (eg, 3:1, 3:2, 2:1, 1:1, 1:2).
[0043] An embodiment of the second aspect of the present application provides an application of the electrolyte of any embodiment of the first aspect in a high-voltage battery.
[0044] In some embodiments, the positive electrode active material of the high voltage battery includes but is not limited to LCO or NCM811.
[0045] In some embodiments, the negative electrode active material of the high voltage battery includes but is not limited to graphite, and may also be various modified artificial graphite and other materials.
[0046] In some embodiments, the charging cut-off voltage of the high-voltage battery is greater than 4.3V (eg, greater than 4.5V, such as 4.3-5V, such as 4.5-4.8V, etc.).
[0047] The following examples are used to further illustrate the advantages and features of the present method, but are not intended to limit the present invention. The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0048] Unless otherwise specified, the quantitative analysis experiments in the following examples were performed three times and the results were averaged.
[0049] Preparation Example 1
[0050] Synthesis of TTMS: 2,2,2-trifluoroethanol (1 equivalent) was mixed with dichloromethane, placed in a 5°C water bath, and stirred for 20 minutes. Triethylamine was then added dropwise to the above mixture and stirred for another 10 minutes. Methanesulfonyl chloride (1.5 equivalents) in dichloromethane was added dropwise to the stirred solvent mixture. The flask was removed from the 5°C bath and the mixture was stirred at room temperature overnight. The reaction mixture was slowly added to a 5% sodium bicarbonate solution and stirred for 20 minutes. Thereafter, the aqueous layer was extracted with dichloromethane. The organic extract was dried and concentrated to a product yield of 90%, and the product was moved to an argon-filled glove box for later use.
[0051] Synthesis of TM: Trifluoromethanesulfonate (12.5 mL, 44.3 mmol) and 2,2,2-trifluoroethanol (6.25 mL, 62.4 mmol) were mixed, stirred at room temperature for 30 min under nitrogen, and then refluxed at 95 ° C. After 4 hours, the mixture was allowed to cool to room temperature, and the excess 2,2,2-trifluoroethanol was distilled to obtain the target molecule in the form of a colorless liquid, and the product was moved to an argon-filled glove box for further use.
[0052] Example 1
[0053] An embodiment of an electrolyte of a high-voltage lithium-ion battery of the present invention and an application thereof, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: first, TM and TTMS are mixed evenly, and then lithium bis(fluorosulfonyl)imide (LiFSI) is dissolved in a TM / TTMS mixed solvent to prepare an electrolyte with a lithium bis(fluorosulfonyl)imide concentration of 1.9M and a TM:TTMS volume ratio of 2:1.
[0054] Example 2
[0055] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the concentration of lithium bis(fluorosulfonyl)imide is 1.5M, and the other conditions remain unchanged.
[0056] Example 3
[0057] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the concentration of lithium bis(fluorosulfonyl)imide is 2.5M, and the other conditions remain unchanged.
[0058] Example 4
[0059] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the volume ratio of TM:TTMS is 1:1, and the other conditions remain unchanged.
[0060] Example 5
[0061] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the volume ratio of TM:TTMS is 3:1, and the other conditions remain unchanged.
[0062] Example 6
[0063] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the volume ratio of TM:TTMS is 1:2, and the other conditions remain unchanged.
[0064] Example 7
[0065] An embodiment of the electrolyte of a high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte of the high-voltage lithium-ion battery described in this embodiment is: the preparation method of the electrolyte is similar to that of Example 1, except that the concentration of lithium bis(fluorosulfonyl)imide is 0.5M or 1M, and the other conditions remain unchanged.
[0066] Comparative Example 1
[0067] A comparative example of the electrolyte of the high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte in this comparative example is: dissolving lithium hexafluorophosphate in a solvent with an EC:DMC ratio of 1 to prepare an electrolyte with a lithium salt concentration of 1M.
[0068] Comparative Example 2
[0069] A comparative example of the electrolyte of the high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte in this comparative example is: dissolving lithium hexafluorophosphate in a solvent with a ratio of EC:DMC:VC of 49:49:2 to prepare an electrolyte with a lithium salt concentration of 1M.
[0070] Comparative Example 3
[0071] A comparative example of the electrolyte of the high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte in this comparative example is: the preparation method of the electrolyte is similar to that of Example 1, except that TM is replaced by trifluoromethyl trifluoromethanesulfonate, and the other conditions remain unchanged.
[0072] Comparative Example 4
[0073] A comparative example of the electrolyte of the high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte in this comparative example is: the preparation method of the electrolyte is similar to that of Example 1, except that TTMS is replaced with trifluoroethyl perfluorobutyl sulfonate or 2,2-difluoroethanol methane sulfonate, and the other conditions remain unchanged.
[0074] Comparative Example 5
[0075] A comparative example of the electrolyte of the high-voltage lithium-ion battery of the present invention and its application, the preparation method of the electrolyte in this comparative example is: the preparation method of the electrolyte is similar to that of Example 1, except that it also contains solvent dimethyl carbonate, and the volume ratio of TM:TTMS:dimethyl carbonate is 2:1:1, and the other conditions remain unchanged.
[0076] Test Example 1
[0077] 1.1 The conductivity of the electrolytes prepared in various embodiments was tested, and the results are shown in Tables 1 and 2 below.
[0078] Method for detecting conductivity: conductivity meter AC impedance method, test voltage 10mV, test frequency 0.01Hz~10KHz.
[0079] Table 1: Li of electrolytes with different lithium salt concentrations of TM:TTMS = 2:1 + Conductivity
[0080]
[0081] Table 2: Li in 1.9M LiFSI in different solvent ratios + Conductivity
[0082] TM:TTMS <![CDATA[Li + Electrical conductivity (mS / cm)]]> TM:TTMS=3:1 (corresponding to Example 5) 4.18 TM:TTMS=2:1 (corresponding to Example 1) 2.53 TM:TTMS=1:1 (corresponding to Example 4) 1.68 TM:TTMS=1:2 (corresponding to Example 6) 1.52
[0083] 1.2 The oxidation stability of the electrolytes prepared in each embodiment was tested by linear sweep voltammetry (LSV). The results are as follows: Figure 3-4 shown.
[0084] Specific methods and conditions for LSV testing: test range is 2~6V, scan rate is 1mV / s.
[0085] Figure 3In the above, the TM:TTMS=3:1 group corresponds to the electrolyte prepared in Example 5, the TM:TTMS=2:1 group corresponds to the electrolyte prepared in Example 1, the TM:TTMS=1:1 group corresponds to the electrolyte prepared in Example 4, and the TM:TTMS=1:2 group corresponds to the electrolyte prepared in Example 6. Figure 3 It can be seen that the electrolytes of Examples 1 and 4-6 have excellent oxidation stability and the current density is less than 0.01 mA / cm 2 .
[0086] Figure 4 The results of the electrolyte oxidation stability test of Example 1 and Comparative Example 2 are shown. Figure 4 It can be seen that the current density of Example 1 is Figure 3 The measured results were consistent and never exceeded 0.01mA / cm 2 , and its oxidation stability is significantly better than that of Comparative Example 2.
[0087] Test Example 2
[0088] 2.1 The electrolytes prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 5 were respectively injected between the MNC811 ternary positive electrode sheet and the graphite negative electrode to assemble a ternary lithium battery (1Ah graphite||NCM811 soft pack battery) for charge and discharge tests. The performance test results are shown in Tables 3 and Figure 2 and 5 .
[0089] The proportion of positive and negative active materials in 1Ah graphite||NCM811 soft pack battery is 95.5% and 94.8% respectively, and the compaction density of positive and negative electrode sheets is 3.4cc respectively. -1 and 1.5cc -1 The N / P ratio is 1.1. The injection volume is 2 g.
[0090] Table 3
[0091] Electrolyte Ni(ppm) Co(ppm) Mn(ppm) Example 1 0.003 0.0004 0.001 Comparative Example 2 0.009 0.001 0.003
[0092] Table 3 shows the dissolution amount of transition metals in the graphite||NCM811 soft-pack battery using the electrolyte prepared in Example 1 or Comparative Example 2 after 100 cycles (25°C 1C charge / 2C discharge, charging cut-off voltage of 4.6V and discharging cut-off voltage of 2.7V).
[0093] Figure 2 The EIS impedance spectra of the graphite||NCM811 soft-pack battery using the electrolytes of Example 1, Comparative Example 1, and Comparative Example 2 after 1000 cycles are shown.
[0094] Figure 5The cycling stability of graphite||NCM811 soft-pack batteries using the electrolytes of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 5 at a cutoff voltage of 4.6V, a charge rate of 1C, and a discharge rate of 2C is shown, wherein the test result of Comparative Example 4 is similar to that of Comparative Example 3 and is not shown here.
[0095] according to Figure 2 and Figure 5 It can be seen that the graphite||NCM811 soft-pack battery using the electrolyte of Example 1 has lower impedance and better cycle performance, which is significantly better than each comparative example.
[0096] 2.2 The positive electrode surface of the graphite||NCM811 soft pack battery using the electrolyte prepared in Example 1 after 100 cycles (25°C 1C charge / 2C discharge charge cut-off voltage is 4.6V discharge cut-off voltage is 2.7V) was detected by X-ray photoelectron spectroscopy (XPS). The results are as follows Figure 1 shown.
[0097] Table 3 and Figure 1 The results show that TM and TTMS decompose during the initial charge and discharge process to generate more protective inorganic Li 2 SO x CEI membrane significantly reduces the dissolution of transition metals in the cathode material.
[0098] Test Example 3
[0099] The electrolytes in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 5 were respectively injected between the LCO positive electrode sheet and the graphite negative electrode to assemble a lithium cobalt oxide soft-pack battery (1Ah graphite||LCO soft-pack battery) for charge and discharge tests. The performance test results are shown in Figure 6 .
[0100] The proportion of positive and negative active materials in a 1Ah lithium cobalt oxide soft-pack battery is 98.6% and 96.7% respectively, and the compaction density of the positive and negative electrodes is 4.1cc respectively. -1 and 1.7cc -1 The N / P ratio is 1.1. The injection volume is 2 g.
[0101] Figure 6 The cycling stability of graphite||LCO soft-pack batteries using the electrolytes of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 5 at a cutoff voltage of 4.55V, a charge rate of 1C, and a discharge rate of 2C is shown, wherein the test results of Comparative Example 4 are similar to those of Comparative Example 3 and are not shown here.
[0102] according to Figure 6 It can be seen that the cycle performance of the graphite||LCO soft-pack battery using the electrolyte of Example 1 is better and significantly better than that of each comparative example.
[0103] High-voltage electrolyte needs to form a stable CEI film on the surface of the positive electrode material to enhance the passivation ability of the surface of the de-lithiation positive electrode material, thereby reducing the side reaction between the positive electrode material and the electrolyte. The organic CEI film formed by the decomposition of traditional EC, DMC and other electrolytes has poor stability and cannot effectively protect the positive electrode material. The TM and TTMS in the fluorinated sulfonate electrolyte prepared in the embodiment of the present application will decompose and generate more protective inorganic Li during the initial charge and discharge process. 2 SO x CEI membrane significantly reduces the dissolution of transition metals in the cathode material ( Figure 1 and Table 3).
[0104] In addition, the high-voltage electrolyte needs to form a stable SEI film with low interfacial impedance on the graphite negative electrode to ensure faster kinetic performance of the battery. The impedance of the SEI film of the battery with the electrolyte of Example 1 of the present application after 1000 cycles is significantly lower than that of Comparative Examples 1 and 2 ( Figure 2 ).
[0105] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0106] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An electrolyte, characterized in that The invention comprises a solvent and a lithium salt, wherein the solvent comprises 2,2,2-trifluoroethyl methanesulfonate (TM) and / or 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
2. The electrolyte according to claim 1, characterized in that The lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI).
3. The electrolyte according to claim 1, characterized in that The electrolyte contains 0.5 to 6 mol / L of lithium salt.
4. The electrolyte according to claim 3, characterized in that The electrolyte contains 0.5 to 3 mol / L of lithium salt.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The solvents are 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS).
6. The electrolyte according to claim 5, characterized in that The solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (5:1) to (1:5).
7. The electrolyte according to claim 6, characterized in that The solvent is 2,2,2-trifluoroethyl methanesulfonate (TM) and 2,2,2-trifluoroethyl trifluoromethanesulfonate (TTMS) in a volume ratio of (3:1) to (1:2).
8. Use of the electrolyte according to any one of claims 1 to 7 in a high voltage battery.
9. The use according to claim 8, characterized in that: The positive electrode active material of the high voltage battery includes LCO or NCM811; optionally, the negative electrode active material of the high voltage battery includes graphite.
10. The use according to claim 8, characterized in that: The cut-off voltage of the high voltage battery is greater than 4.3V.
Citation Information
Patent Citations
High-voltage stable electrolyte for lithium-ion battery
CN105449277A
Lithium metal battery electrolyte and lithium metal battery
CN112216865A
High-safety electrolyte and preparation method and application thereof
CN113871720A
Wide-temperature high-voltage lithium ion battery electrolyte and lithium ion battery containing electrolyte
CN116365042A
Electrolyte and lithium ion battery containing same
CN118763286A
